How Often Is End-of-Life Care in the United States Inconsistent with Patients' Goals of Care? - Khandelwal, Nita; Curtis, J Randall; Freedman, Vicki A; Kasper, Judith D; Gozalo, Pedro; Engelberg, Ruth A; Teno, Joan M (Journal of palliative medicine, 2017)
Despite its importance, little is known about the prevalence of, and factors associated with, end-of-life care that is consistent with patients' wishes. To document the proportion of bereaved respondents who reported care inconsistent with patients' wishes and characterize the predictors of end-of-life care associated with inconsistent care. Retrospective analysis of nationally representative survey data of persons aged >65 years. Settings/Subjects: Bereaved family members responding to the last month of life component of the National Health and Aging Trends Study. Methods/Measurements: Bereaved family members assessed treatment decisions and their consistency with patients' wishes, unmet needs, and quality of care. We examined differences between patients receiving inconsistent versus consistent care. A total of 1212 family members were interviewed, representing (when weighted) 4.8 million decedents. Thirteen percent stated that care was inconsistent with decedent's wishes. Consistent care was unassociated with patient's sex, age, or race/ethnicity. Death at home was more likely to represent consistent care, and death in the hospital or nursing home was more likely to represent inconsistent care (p = 0.052). Respondents reporting inconsistent care were more likely to rate the quality of care as fair or poor (19.1% vs. 4.8%, p < 0.001), reported more unmet needs for pain management (30.5% vs. 19.4%, p = 0.037), and reported more concerns with communication (29.8% vs. 17.0%, p = 0.003). One in eight respondents stated care in the last months of life was inconsistent with patients' wishes; such care was associated with worse ratings of care, pain management, and communication with clinicians.